SCHIZOPHRENIA AND PSEUDOBULBAR AFFECT DISORDER IN THE FILM SCRIPT JOKER - Alfina Eka Pratiwi; Much Koiri (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2022)
This study deals with schizophrenia, pseudobulbar affect (PBA) and negative responses of the community experienced by the main character of the Joker 2019 film, Arthur Fleck and the public's response to his illness. schizophrenia is a condition in which a person cannot distinguish between the real world and the world of fantasy or hallucination; while pseudobulbar affect (PBA) is a condition characterized by uncontrollable laughing or crying.Descriptive qualitative method to reveal the social features is applied to get relevant and precise data concerning the discussion based on the clinical psychology theory. Cinematography by listening to every scene in the film, showing Arthur Fleck's illness and the public's response to his illness is then used for the data collection procedures. The results show that the main character has got schizophrenia in the form of hallucination and pseudobulbar affect (PBA) in the form of inability to control his laughter and at the same time it is also found that the community gives negative responses upon the mental illness of the main character.